Políticas públicas de acesso ao ensino superior como medida concretizadora de direitos fundamentais - Evangelista, Juliana Pedroza Carvalho (2019)
Public policies emerge, as real instruments for the realization of fundamental rights, linking more directly to social rights. Thus, when the State decides to make use of affirmative policies, it acts to provide the exercise of rights by those who alone could not. Thus, the use of public policies that guarantee access to higher education is necessary, and they have the role of democratizing higher education. There are different policies for this purpose, such as the Unified Selection System (SISU), Student Financing (FIES), the University for All Program (PROUNI) and the Quotas Law. However, this paper will analyze only two public policies: the Quotas Law and Student Financing (FIES). With regard to quotas in Brazilian public universities, it is observed that they are based on the social and / or racial element. What implies in the previous conclusion, that the quota policy as formulated in Law 12.711 / 2012, is of the social type. However, the aspect that continues to raise questions, is still the racial, more precisely, the proof of the racial condition. The concern is whether self-declaration / self-identification can be considered as a skillful criterion for its intended purpose. Student financing (FIES) has facilitated access to higher education. Although this policy was specific for students in private institutions, its growth was size, which became the main responsibility for accessing private IES. It turns out that, unlike in basic education, private higher education accounts for the vast majority of enrollments in this stage of education. Thus, the FIES has, to a certain extent, worked as a stimulus to the expansion of large educational groups. Both policies, quotas and FIES, realize the realization of one of the most valuable rights, given that access to education allows the individual to be the owner of their own history, bringing individual and collective benefits. In turn, public policies must provide due security in all its stages, in addition to not departing from its primary purpose, realization of rights, otherwise it will serve particular interests, sacrificing the collective, since the benefits provided by the access to education are extended to the whole community. In this work, it was adopted as exploratory method, seeking to understand and explore in a detained way the foundations for the implementation of public policies, analyzing the factual and legal elements that justify it. Regarding the approach to the problem, qualitative research is chosen, since it better serves the purpose of understanding the adoption and reflexes of public policies for access to higher education (FIES and Quota Law). As for the type of research, bibliographical and documentary will be used. For the bibliographic research, theses, dissertations, books, periodicals and scientific publications on the subject were consulted. In documentary research, the following sources were consulted: legal documents pertinent to the creation and alterations of the Fies and the Law of Quotas, Federal Constitution, laws, resolutions, decrees, ordinances, manuals and technical surveys related to the subject.